Cost-Effectiveness of Quadrivalent Human Papillomavirus Vaccination in Adolescent Girls in Russian Federation - Alla V. Rudakova; Susanna M. Kharit; Lyudmila V. Lyalina; Alla S. Lisianskaya; Svetlana A. Protsenko; Irina V. Mikheeva; Aleksandr N. Uskov; Yurii V. Lobzin (Педиатрическая фармакология)
The human papillomavirus (HPV) infection is one of the major risk factor of development of genital warts, a cervical dysplasia, a cervical cancer, and also some other oncologic diseases. The usage  of quadrivalent HPV vaccine in girls reduces the corresponding case  rate and the mortality significantly.The objective of this study is to analyze the cost-effectiveness of quadrivalent HPV vaccination cases of 12-year-old girls in Russian Federation.Methods. A Markov model is used on the basis of epidemiological data in Russian Federation. In base case the cost-effectiveness was  estimated from societal perspective. We assumed that the effect of  vaccination remains throughout all life. The analysis is performed for survival of 12-year-old girls. We considered only effect in the  vaccinated population. Costs for therapy of the diseases associated  with HPV infection corresponded to compulsory health insurance  rates across St. Petersburg for 2017. Costs and life expectancy have been discounted for 3.5% a year.Results. Quadrivalent HPV vaccination of 12-year-old girls in Russian Federation will allow to prevent counting on 100 000 the  vaccinated persons 2918 cases of genital warts, 5095 cases of  cervical dysplasia, 893 cases of invasive cervical cancer, 56 cases of  vulvar cancer, 18 cases of vaginal cancer, 13 cases of anal cancer, 7  cases of oropharyngeal cancer. The vaccination will provide cost  reduction, caused by HPV-associated diseases, for 453.9 million  rubles on 100 000 vaccinated, and 86.5% of the predicted prevented costs will be caused by decrease in incidence of cervical cancer, 9%  — cervical dysplasia, 2.9% — genital warts. The quadrivalent HPV vaccination is associated with an incremental cost-effectiveness ratio (ICER) of 247 560 rubles per quality adjusted life-year (QALY) and  334 200 rubles per life-year gained (LYG). Thus, in both cases, cost  effectiveness of rotavirus vaccination per 1 QALY will not exceed the  generally accepted threshold willingness-to-pay equal to three times  the gross domestic product in Russia (2016 — 1.76 million RUB).Conclusions. Quadrivalent HPV vaccination of girls prior to the beginning of sex life could be considered in Russian Federation as an economically effective technology for preventing HPV-associated diseases.